Nilai Pendidikan Karakter Jawa dalam Muatan Lokal Batik - Syarifatul Muna; Ahmad Shofiyuddin Ichsan (Educational and Talent Development Center of Indonesia, 2022)
This research aimed to describe a character education model based on Javanese wisdom through the implementation of local batik content for MI Ma'arif Pijenan Bantul Yogyakarta students and its relevance to contemporary character education. The research method used was descriptive qualitative, while the research data sources were obtained from observations, interviews, and documentation. The research results showed that: (1) the implementation of the local content of batik in this school included several things, namely: first, processing mori cloth before making batik, then nganji and followed by the ngemplong stage. Second, the batik process began with making patterns, preparing batik wax, then the stage of cutting and coloring the cloth. Third, removed wax from the cloth. (2) The results of the implementation could be understood that children were more socially sensitive, more empathy, more serious, more able to save money, more able to be careful, and more able to be careful in making batik. (3) Supporting factors in the implementation of these activities, namely: the existence of a batik center in the school environment, the support of the school's academic community, the existence of cohesiveness and a sense of optimism in students. The inhibiting factors were: the lack of teachers in guiding and focusing on teaching batik, not enough time, and students' boredom with batik activities.